Comprehensive analysis of compound drought and heatwave events in China over recent decades based on regional event identification algorithm - Liu Jinping; Li Mingzhe; Liu Tie; Ren Yanqun; Hu Qingfeng; Masoud Jafari Shalamzari; Quoc Bao Pham; He Peipei (International Journal of Digital Earth)
The frequency and intensity of Compound Drought and Heatwave Events (CDHEs) have significantly increased under global change, extensively impacting societies and ecosystems. This study aims to identify CDHEs and thoroughly analyze their characteristics and trends. By combining the Standardized Precipitation Evaporation Index (SPEI) and Heatwave Index (HWI), a Compound Drought and Heatwave Index (CDHI) is developed. The regional event identification algorithm, Intensity-Area-Duration (IAD), is applied for CDHE detection. Analysis of warm-season CDHEs (May–October) reveals a notable rise in frequency and duration, particularly after 2000 across China. High-prevalence areas include Northwest China (especially central and eastern Xinjiang) and the Southeast. In addition to frequency and number of days, the intensity, duration, and impact area of CDHEs all showed increasing trends, with relatively consistent spatial distribution patterns. The intensity, duration, and impact area of CDHEs in the Northwest and Southern regions were higher than in the Northeast. A notable positive correlation was found between intensity, duration, and impact area, suggesting that longer durations are associated with higher intensity and larger impact areas. These findings are valuable for enhancing disaster risk reduction and climate change adaptation. In light of growing CDHE severity, a strategy emphasizing mitigation while equally addressing adaptation is essential.